2016
DOI: 10.1038/nprot.2016.125
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced iodination of aryl halides under very mild conditions

Abstract: Aryl iodides are important precursors in synthetic chemistry that form carbon–carbon and carbon–heteroatom bonds. Most methods use transition-metal catalysts, which need to be scrupulously removed before the compounds can be used in the pharmaceutical and electronics industries, where only parts-per-million levels of transition metals are allowed. The aromatic Finkelstein iodination reaction is a powerful method of preparing valuable aryl iodides from cheap but less reactive aryl bromides and chlorides. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Therefore, a catalytic cross-dehydrogenative Minisci alkylation without stoichiometric chemical oxidants is long-sought-after 39 . Our group has a long-term interest in the arene functionalisation, which was facilitated by the excited aromatics under catalyst-free conditions [42][43][44][45][46][47] . Recently, we documented a simple and clean Minisci alkylation reaction via formal dehydrative coupling of heteroarenes with alcohols.…”
mentioning
confidence: 99%
“…Therefore, a catalytic cross-dehydrogenative Minisci alkylation without stoichiometric chemical oxidants is long-sought-after 39 . Our group has a long-term interest in the arene functionalisation, which was facilitated by the excited aromatics under catalyst-free conditions [42][43][44][45][46][47] . Recently, we documented a simple and clean Minisci alkylation reaction via formal dehydrative coupling of heteroarenes with alcohols.…”
mentioning
confidence: 99%
“…It has been documented that triplet carbonyls can abstract hydrogen atoms, especially those adjacent to heteroatoms (such as the O atom in ethers and alcohols), to produce the hydroxyalkyl radical. 44,45 Inspired by this and following our continued interest in photochemistry as a greener alternative to traditional transition-metal-catalyzed chemistry, [46][47][48][49][50][51][52][53][54] we anticipated that simply adding ketones into the reaction system would increase the generation rate of hydroxymethyl radical 15 (,CH 2 OH) because, under light irradiation, triplet ketone would be able to abstract the a-H of MeOH efficiently, 45 eventually leading to the efficient formation of direct-methylation product (16). Different from Jin and MacMillan's system 34 involving iridium photo-redox catalyst and odorous thiol organocatalyst, both of which are either expensive or not friendly to handle, we expected this system to avoid external catalysts and be driven solely by the solvent's intrinsic properties (Scheme 2B).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, nicotine cannot be methylated under the current conditions (49). Although the C1 position of isoquinolines can be methylated (33 and 34), it was found that the isoquinoline with C1 position occupied could not be further functionalized, which suggests that the C3 position of isoquinoline is inert to this method (50). Finally, heteroaryl bromide 51 was subjected to the standard conditions.…”
Section: Scope Of the Investigationmentioning
confidence: 99%
“…In this regard, Li has recently developed a protocol for photo-induced generation of aryl radicals from aryl (pseudo)halides through single-electron-reduction of their photo-excited state by an iodide ion. [14] The resulting aryl radicals undergo coupling reactions with molecular iodine (I 2 ) (Scheme 2A) or bis(pinacolato)diborane (B 2 pin 2 ) (Scheme 2B), and 5-exo cyclization with a pendant alkene followed by iodination of the resulting alkyl radicals. The same group also reported photoinduced synthesis of aryl phosphonates from aryl halides and H-phosphonates in the presence of NaOt-Bu, in which single-electron-reduction of photoexcited aryl halides by in-situ generated sodium phosphite/phosphinite may operate to initiate the ensuing radical coupling process (Scheme 2C).…”
Section: Introductionmentioning
confidence: 99%